The psychological diagnosis of panic disorder - Bourenane, Samiya; Ghoumres, Abdelmalek (Technium Social Sciences Journal, 2022)
Psychological disorders are common among society individuals because of life stresses’ accumulations, which differ in terms of diagnosis,categorization and the reasons behind them. This makes them difficult in terms of diagnosis and understanding. Therefore, psychologists have to examine them for the sake of identifying their types, according to psychological and social examinations. The disorders interfere with anxiety and the concerns of panic disorder, which is categorized as an independent pathological category characterized with frequent seizures with subsequent physical signs. This is what we shall explain through this article.